Economic and Environmental Sustainability: The Impact of Indonesia-China Maritime Partnership on Indonesia’s Maritime Sector - Wulandari, Diah Ayu (Jurnal Sains Sosio Humaniora, 2024)
This study analyzes to disclose the Indonesia-China maritime relationship may achieve a balance between economic growth and sustainable environmental practices. This study also aim to analyze the impact of Indonesia-China maritime partnership on Indonesia’s maritime sector. This study are described qualitatively and analyzed using the theoretical framework of blue economy and sustainable development. The findings of this study emphasize that the economic and environmental sustainability aspects are firmly upheld in Indonesia-China partnership in the maritime sector. The many justifications from Indonesia-China maritime partnership demonstrate that Indonesia-China maritime partnership considers economic and environmental sustainability in addition to short-term benefits. The study findings also indicate that Indonesia-China maritime partnership significantly effects economic and environmental sustainability in Indonesia’s maritime sector. The Indonesia-China decades-long relationship facilitates two countries' partnership.